2017
DOI: 10.1080/1028415x.2017.1397875
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioural effects of Lactobacillus rhamnosus GG alone and in combination with prebiotics polydextrose and galactooligosaccharide in male rats exposed to early-life stress

Abstract: Early life is a period of significant brain development when the brain is at its most plastic and vulnerable. Stressful episodes during this window of development have long-lasting effects on the central nervous system. Rodent maternal separation (MS) is a reliable model of early-life stress and induces alterations in both physiology and behaviour. Intriguingly, the gut microbiota of MS offspring differ from that of non-separated offspring, suggesting a mechanistic role for the microbiota-gut-brain axis. Hence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 49 publications
1
48
0
Order By: Relevance
“…Notably, this is the first study to show that MFGM consumption results in a significant reduction of the early‐life stress‐induced visceral hypersensitivity. While previous studies have shown that dietary supplementation with probiotics and prebiotics is effective in the reduction of visceral sensitivity (Kannampalli et al., ; McKernan, Fitzgerald, Dinan, & Cryan, ; McVey Neufeld et al., ; Wang et al., ), the impact of MFGM has not been shown before.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Notably, this is the first study to show that MFGM consumption results in a significant reduction of the early‐life stress‐induced visceral hypersensitivity. While previous studies have shown that dietary supplementation with probiotics and prebiotics is effective in the reduction of visceral sensitivity (Kannampalli et al., ; McKernan, Fitzgerald, Dinan, & Cryan, ; McVey Neufeld et al., ; Wang et al., ), the impact of MFGM has not been shown before.…”
Section: Discussionmentioning
confidence: 96%
“…Aspects of central nervous system development such as hippocampal learning are impacted upon by stressors in early‐life (McVey Neufeld et al., ). Here we noted that MFGM alone and combined with the prebiotic blend was sufficient to improve spatial learning in MS rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L . rhamnosus GG in combination with polydextrose reverses early life stress‐induced effects on anxiety behavior in the open field, learning in the Morris Water Maze & hippocampal GABA receptor mRNA (McVey Neufeld et al, ). Most recently, probiotic administration has been shown to reverse the sex‐dependent ELS‐induced effects of maternal separation on pubertal timing (Cowan & Richardson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Maternal separation during early life disrupted the microbiota of the offspring of rhesus monkeys and rats [149, 150]. Interestingly, a diet containing prebiotics in combination with live Lactobacillus rhamnosus GG attenuated the effects of early-life maternal separation on anxiety-like behaviour and hippocampal-dependent learning [151]. Germ-free mice were more vulnerable to restraint stress, resulting in higher adrenocorticotropic hormone and corticosterone in plasma [14, 16], a reduction in glucocorticoid receptor mRNA and an increased stress response [14].…”
Section: Early Postnatal Perturbations Of the Microbiotamentioning
confidence: 99%